2017
DOI: 10.1590/1678-4685-gmb-2016-0297
|View full text |Cite
|
Sign up to set email alerts
|

DNA sampling from eggshells and microsatellite genotyping in rare tropical birds: Case study on Brazilian Merganser

Abstract: This study shows that sampling maternal DNA from hatched and abandoned eggshells is a viable noninvasive strategy for studying the genetics of rare or endangered tropical birds, as exemplified here by the Brazilian Merganser (Mergus octosetaceus). Eighteen microsatellites were isolated from enriched libraries and nine heterologous loci from related species were tested. Seven loci were amplified successfully, with five of them being polymorphic. These loci exhibited amplicons ranging from 110 to 254 bp for 132 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…In birds, eggshells (Strausberger and Ashley 2001, Egloff et al 2009, Kjelland and Kraemer 2012, Maia et al 2017 or feathers (Rudnick et al 2007, Kjelland and Kraemer 2012, Olah et al 2016) can be used as a source of DNA. Feathers can be collected opportunistically or through a feather-trap (Maurer et al 2010).…”
Section: Dna Samplingmentioning
confidence: 99%
“…In birds, eggshells (Strausberger and Ashley 2001, Egloff et al 2009, Kjelland and Kraemer 2012, Maia et al 2017 or feathers (Rudnick et al 2007, Kjelland and Kraemer 2012, Olah et al 2016) can be used as a source of DNA. Feathers can be collected opportunistically or through a feather-trap (Maurer et al 2010).…”
Section: Dna Samplingmentioning
confidence: 99%
“…The pattern of differentiation found by the seven individuals from the Canastra (CAN211, CAN228, CAN235, CAN237, CAN239, CAN242, and CAN243) and the five captive individuals (MO238, MO241, MO246, MO255, and MO256) can be explained by the fact that these individuals are from the Canastra or descendants of individuals from this area and that the captive population is composed of approximately 70% of individuals from Jalapão, Paranaíba, and their descendants, which can maximize the differences. Furthermore, of all the remaining Brazilian Merganser populations, the Canastra is the one with the greatest genetic diversity [10], which may make these individuals more differentiated from the others, and since little is known about the mode of dispersal of the species and there is no data on dispersal or migration of individuals over long distances [52], a slight difference between populations is expected. To calculate the effective population size (Ne), we considered all captive individuals as a single "population" (the captive pool), since sample sizes smaller than 30 can potentially influence the Ne estimates [51].…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian Merganser captive population was established in the last decade at Zooparque Itatiba in São Paulo state, Brazil, and in 2019, it was composed of 46 mergansers that included 19 founding individuals that came originally from eggs collected in nature and 27 individuals that were born from ex situ crosses. Since its start, the Brazilian merganser captive breeding program has been genetically monitored by our research group, which previously published some genetic studies of the wild merganser populations [9][10][11][12][13]. All these studies identified a low diversity and high inbreeding in the wild populations, although with some interpopulation diversity [13].…”
Section: Introductionmentioning
confidence: 99%
“…53,54 Eggs were used as source of DNA for the molecular identification of three Neotropical parrot and one owl species victims of illegal traffic, 37 and to assess the genetic diversity of the critically endangered Brazilian Merganser ( Mergus octosetaceus ). 40 Bird carcasses were used as source of DNA for molecular identification of the species involved in collisions with terrestrial vehicles. 49,50 In cases such as these, when the physical deterioration of the remains preclude a reliable morphological identification of the species killed, the molecular identification is usually the only alternative.…”
Section: Discussionmentioning
confidence: 99%